ANALISIS PENGARUH PENYEMPITAN JALUR JALAN TERHADAP KARAKTERISTIK ARUS LALU LINTAS (STUDIKASUS : Jembatan Ayek Betung Jl. Kapten Sanap Kota Pagar Alam) - m. Gery perliansya; Dyan Pratnamas; Ali Okta Akbar (JURNAL ILMIAH BERING'S, 2019)
On several roads in the city of Pagar Alam the road narrowing occurred. In particular, on Bridges often cause problems such as congestion, queues, and delays, it is necessary to know the behavior of traffic flow characteristics such as Volume, Speed, and Density. The primary data survey on the Ayek Bridge section of Jalan Kapten Sanap, Pagar Alam City, was carried out for two Sundays and Mondays with the Manual Count method. Data analysis was based on the 1997 Indonesian Road Capacity Manual (MKJI) using Microsoft Excel software. As for the results of the study obtained the traffic volume for road type 4/2 D (before narrowing) road capacity of 5,643 pcu / hour perlajur, with a value of degree of saturation of 0,15 and service level Type A. Road type 2/2 UD (narrowing) road capacity of 2375 pcu / hour perlajur, with a value of Saturation 0.38 and Service Level Type A, 4/2 UD type road (After Refinement) road capacity of 5130 pcu / hour of service, with a value of 0.20 saturation and level Type A service. The biggest shock wave is obtained on Monday at 07.00-08.00 WIB which is -119.18 km / hour. Negative value is a backward forming shock wave, a backward shock wave occurs towards the arrival of the vehicle. The term 'retreat' means that with time, the shock wave will move backward (upstream or in the direction opposite to the traffic perger). The term 'formed' means that with time, congestion will increase upstream.